PERAN TEKNOLOGI INFORMASI TERHADAP MOTIVASI BELAJAR SISWA SMKN 1 KOTA BIMA - Suci Putri; Sri Rahmawati; Gunawan Akbar; Jannah, Miftahul; Khairunnis (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2024)
This service is based on the influence of technology on students' learning motivation because technology is increasingly spread everywhere and has a big impact on people's lives, especially in society and the educational environment, especially in vocational high schools. Daily life is experiencing major changes due to technological advances. With this dedication and research, the PKM team wants to know how technology influences student learning motivation in the Computer and Network Engineering (TKJ) and RPL (Software Engineering) departments of SMKN 1 Bima City. The purpose of this service is to display and explain the role of information technology in student learning motivation. This service is carried out through conducting field surveys. 78 students were research subjects. There is a positive correlation between the use of information technology and student learning motivation, according to PKM's findings. This shows that students' desire to learn increases with more intensive use of information technology.